Differential chemotherapeutic regimen cytotoxicity against pancreatic cancer stem cells: a preliminary in vitro study - Doello González, Kevin; Francisco J.Quiñonero; Perazzoli, Gloria; Gago, Lidia; Chico, María Ángeles; Mesas, Cristina (Ars Pharmaceutica (Internet), 2021)
Introduction: Pancreatic cancer treatment in advanced stages is based on different chemotherapy regimens. Cancer stem cells are responsible for tumor chemoresistance and recurrence in adjuvant and metastatic settings. The objective of this article was to evaluate how these chemotherapeutic regimens affect the proportion of cancer stem cells and the expression of stemness markers. Method: We used the pancreatic adenocarcinoma cell line PANC-1 as a model to apply different chemotherapeutic protocols (monotherapy and combined therapy) using 5-Fluorouracil, Oxaliplatin, Irinotecan, Gemcitabine and Abraxane. Results: After analyzing different tumor stem cell markers (SOX2, OCT4, CD133, CD44 and CD24) in pancreatic cancer cells treated with different chemotherapeutic protocols by means of RT-qPCR, Oxaliplatin and Gemcitabine in monotherapy were the chemotherapies that selected the most cancer stem cells while the FOLFIRI protocol decreased them. Conclusions: Regarding the selection of markers, it has been much higher in the case of Gemcitabine alone. In conclusion, these findings could improve and personalize pancreatic cancer therapy.